Small intestinal bacterial overgrowth syndrome (SIBO) - clinical manifestations, diagnosis and therapeutic options - Dobrzeniecki, Krzysztof; Olesińska, Natalia; Pachla, Magdalena; Grzegorczyk, Aleksandra; Muc, Katarzyna; Hopej, Natalia; Turek, Kacper (Quality in Sport, 2024)
Small intestine bacterial overgrowth (SIBO) is a gastrointestinal disorder characterized by an abnormal growth of bacterial populations within the small intestine. These conditions disrupt the balance of microorganisms in the gastrointestinal tract, leading to a variety of clinical symptoms and complications. Excessive bacterial proliferation in the small intestine often results from impaired motility, anatomical abnormalities or changes in the immune system. These factors contribute to the fermentation of undecomposed carbohydrates, leading to the production of gasses and toxic by-products, causing symptoms such as abdominal pain, bloating, diarrhea and malabsorption. A variety of diagnostic methods, including breath tests and small bowel aspirate cultures, are used to accurately identify excessive bacterial growth. Treatment of SIBO involves a multidisciplinary approach, including dietary modifications, antibiotic therapy and prokinetic agents. Antibiotic treatment remains the cornerstone of therapy, but relapses require a focus on identifying and eliminating predisposing factors.